2002
DOI: 10.1128/iai.70.11.6188-6195.2002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immune Impact of Mycobacterium bovis BCG Vaccination Scarring

Abstract: The World Health Organization recommends Mycobacterium bovis BCG vaccination in areas of high tuberculosis prevalence. BCG's clinical and immune effects, not necessarily Mycobacterium tuberculosis specific, are unclear. BCG vaccine scarring often is used as a surrogate marker of vaccination or of effective vaccination. We evaluated BCG scarring status in relation to clinical findings and outcome in 700 hospitalized Malawians, of whom 32 had M. tuberculosis bloodstream infections (BSI) (10 of whom had cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…25,26 However, there is an increasing number of studies indicating that BCG might also induce immune-regulatory responses. A recent study has revealed higher IL-10 production in systemic T cells and monocytes of BCG-vaccinated children, 14 which suggest activation of the anti-inflammatory immune axis. Furthermore, a study of TB patients and healthy BCG-vaccinated subjects has shown elevated pro-as well as anti-inflammatory cytokines by PBMCs in response to MTB antigens, represented by higher levels of IFN-c, TNF-a and IL-10 in both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 However, there is an increasing number of studies indicating that BCG might also induce immune-regulatory responses. A recent study has revealed higher IL-10 production in systemic T cells and monocytes of BCG-vaccinated children, 14 which suggest activation of the anti-inflammatory immune axis. Furthermore, a study of TB patients and healthy BCG-vaccinated subjects has shown elevated pro-as well as anti-inflammatory cytokines by PBMCs in response to MTB antigens, represented by higher levels of IFN-c, TNF-a and IL-10 in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the infants with a BCG scar had higher anti-inflammatory responses, represented by higher ratios of interleukin-10 (IL-10)-producing to IL-4-producing T cells, as well as higher ratios of IL-10-producing to IL-6-producing monocytes in their blood. 14 These results might suggest that BCG vaccination early in life leads to a more robust regulatory network, which prevents excessive inflammatory responses associated with overt pathology, organ failure and death.…”
Section: Introductionmentioning
confidence: 97%
“…The serum retinol concentration was measured at the time of follow-up and children were classified as VA severely deficient (serum retinol ,0.35 mmol/L), VA deficient (serum retinol ,0.70 mmol/L), or normal (serum retinol $0.70 mmol/L) (79). The authors reported that significantly more children with VA deficiency had a visible scar generated by BCG than children with normal VA status.…”
Section: Va and Vaccine Responsesmentioning
confidence: 99%
“…TB is the greatest cause of death due to a single pathogen, and it is a leading killer among people infected with human immunodeficiency virus or AIDS. Mycobacterium bovis bacillus Calmette Guérin (BCG) is the only vaccine available for clinical use and protects children against miliary tuberculosis (13); however, it has shown variable levels of efficacy against pulmonary TB, as demonstrated by several clinical trials (7). For example, a major trial in The United Kingdom showed Ͼ75% protection (9); however, trials in south India and Malawi demonstrated that BCG fails to consistently protect against pulmonary TB (7,19).…”
mentioning
confidence: 99%